2021
DOI: 10.1111/jth.15296
|View full text |Cite
|
Sign up to set email alerts
|

Heparins have adequate ex vivo anticoagulant effects in hospitalized patients with cirrhosis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interestingly, however, VTE prophylaxis also does not seem to decrease VTE rates in these retrospective studies, suggesting that the prophylactic regimens administered are suboptimal. Although in vitro studies have suggested a decreased potency of some anticoagulant drugs in patients with liver disease, 61 in a recent prospective study, a single dose of prophylactic heparins led to a similar decrease in thrombin generation in patients with chronic liver disease compared to patients without liver disease 62 . Although future studies on the prolonged use of VTE prophylaxis and its optimal dosages should be performed, VTE prophylaxis should not be withheld from patients with cirrhosis.…”
Section: Haemostatic Complications In Liver Diseasementioning
confidence: 99%
“…Interestingly, however, VTE prophylaxis also does not seem to decrease VTE rates in these retrospective studies, suggesting that the prophylactic regimens administered are suboptimal. Although in vitro studies have suggested a decreased potency of some anticoagulant drugs in patients with liver disease, 61 in a recent prospective study, a single dose of prophylactic heparins led to a similar decrease in thrombin generation in patients with chronic liver disease compared to patients without liver disease 62 . Although future studies on the prolonged use of VTE prophylaxis and its optimal dosages should be performed, VTE prophylaxis should not be withheld from patients with cirrhosis.…”
Section: Haemostatic Complications In Liver Diseasementioning
confidence: 99%
“…There have been concerns raised from preclinical studies regarding efficacy of these agents in patients with cirrhosis due to their indirect mechanism of action via potentiation of antithrombin, which is reduced in cirrhosis 53 . However, a recent study comparing the anticoagulant effect of prophylactic LMWH/UFH prescribed to patients with and without cirrhosis suggested a similar anticoagulant effect of heparins in patients with cirrhosis 54 . There is no need for routine laboratory monitoring in this setting.…”
Section: Choice Of Pharmacological Thromboprophylaxis In Patients Wit...mentioning
confidence: 99%
“…53 However, a recent study comparing the anticoagulant effect of prophylactic LMWH/UFH prescribed to patients with and without cirrhosis suggested a similar anticoagulant effect of heparins in patients with cirrhosis. 54 There is no need for routine laboratory monitoring in this setting. As highlighted above and in Table 1, not all studies reported the pharmacological agent and/or doses utilized, so specific recommendations regarding preferred agent/dose cannot be made.…”
Section: Choice Of Pharmacologic Al Thromboprophyla Xis In Patient S ...mentioning
confidence: 99%
“…97 Nevertheless, in a recent study performed by our group, it was shown that heparins have comparable anticoagulant effects in patients with ACLF as in those with cirrhosis or nonliver hospitalized, suggesting that the doses as currently used in patients without underlying liver disease might equally be suitable for those with ACLF. 99…”
Section: Correction Of Altered Hemostasis In Acutely Ill Liver Patientsmentioning
confidence: 99%